Differential Effects of Tango Versus Dance for PD in Parkinson Disease - McNeely, Marie E.; Mai, Marina M.; Duncan, Ryan P.; Earhart, Gammon M. (Frontiers in Aging Neuroscience, 2015)
Over half of the general population does not achieve recommended daily levels of physical activity, and activity levels in people with Parkinson disease (PD) are lower than in healthy older adults. Dance can serve as an adjunct to traditional treatments to improve gait, balance, and quality of life in people with PD. This study directly compares a tango dance intervention and a dance intervention based on the Dance for PD model which integrates multiple dance styles. Eleven people with PD participated in a community-based mixed styles dance intervention called Dance for Parkinson’s (D4PD). Participants in the D4PD group were matched to participants in an ongoing community-based exercise study who participated in tango dance. The groups received 12 weeks of intervention, attending one-hour group classes twice a week. Participants were evaluated off anti-PD medication before and after intervention. Measures of balance, repeated sit-to-stand performance and endurance (Mini-BESTest, four square step test, five times sit to stand, six minute walk time) improved from pre to post similarly in both groups. Motor sign severity (MDS-UPDRS-III) and functional mobility (TUG) improved in the tango group and worsened in the D4PD group. Gait velocity was not affected by either intervention. Direct comparisons of different interventions are critical for developing optimal exercise interventions designed to specifically target motor impairments in PD. Tango dance interventions may preferentially improve mobility and motor signs in people with PD, compared to D4PD.